Kajian Literatur : Etnografi Digital Sebagai Cara Baru Dalam Pencarian Data Dalam Proses Perencanaan Arsitektur - Effendi, Andrey Caesar; Purwanto, LMF (Aksen : Journal of Design and Creative Industry, 2021)
The use of digital technology today can be said to be inseparable in our daily lives. Digital technology is slowly changing the way we communicate with others and the environment. Socialization that is usually face-to-face in the real world now can be done to not having to meet face-to-face in cyberspace. This literature review aims to see a change in the way of obtaining data that is growing, with the use of digital technology in ethnographic methods. The method used in this paper is to use descriptive qualitative research methods by analyzing the existing literature. So it can be concluded that the use of digital ethnography in the architectural programming process can be a new way of searching for data at the architectural programming stage.